Forms of Cooperative Learning in Language Teaching in Slovenian Language Classes at the Primary School Level - Alenka Rot Vrhovec (Center for Educational Policy Studies Journal)
In the Slovenian language syllabus, teachers are recommended to provide a greater share of group work during class. During types of learning such as cooperative learning in smaller groups or pairs, students actively develop communicative competence. The present article presents a survey that attempted to determine whether teachers from the first to the fifth grade execute cooperative learning in language classes. The purpose of the article is to raise teachers’ awareness and encourage them to design and execute cooperative learning more frequently.